Understanding lay conceptions of workplace criers: a prototype analysis - Tan, Terri Su-May (Nanyang Technological University, 2022)
Crying has been argued to be the most intense emotional expression in the workplace, and observers’ conceptions of workplace criers can impact important employee outcomes, such as their collaborative relations with co-workers, performance evaluations, and career progression. Despite this, prior assessments of such conceptions have been limited to several crier features pre-selected by scholars (e.g., warmth, competence), rendering observers’ range of conceptions largely unexamined. Scholars also posit that observers naturalistically ascribe certain features to workplace criers faster than others (e.g., emotionality before competence), which suggests how some features might be better descriptors of criers than others. This, however, has not been verified in extant literature. These issues present crucial gaps in this nascent area of research, and potentially compromise validity when subsequently predicting downstream consequences for workplace criers. They also suggest that the concept of workplace criers is prototypically organised, comprising an extensive range of crier features where some are more central to the concept than others. To investigate this possibility, four studies utilising the prototype approach were conducted with full-time employees in Singapore. In Study 1 (n = 163), participants freely listed their conceptions of workplace criers, which were coded into 51 features of differing frequency. Study 2 (n = 97) comprised a prototypicality rating task, where participants judged how well each feature characterised workplace criers. A wide distribution of ratings emerged, which was comparable to those of previously examined prototype concepts. Features receiving high prototypicality ratings were thereafter classified as central to workplace criers, while features receiving low prototypicality ratings were classified as peripheral. Prototypicality ratings were also positively related to the feature frequencies obtained in Study 1, supporting the notion that feature prototypicality is associated with ease of recall. Next, a reaction time (RT) task in Study 3 (n = 162) showed that participants were quicker to confirm central features (e.g., “Stressed”, “Sensitive”) as typical of workplace criers, compared to peripheral features (e.g., “Incompetent”, “Unmotivated”). Moreover, they were quicker to disconfirm peripheral features as typical of workplace criers, compared to central features. These findings corroborated the prototype structure by demonstrating its impact on implicit cognition. Lastly, in further examining central features of workplace criers, an RT task in Study 4 (n = 107) assessed if individual central features were implicitly gendered in nature (i.e., whether each feature would be more rapidly associated with a male or female workplace crier). Results did not support the gendered nature of central features. Collectively, this thesis explicates how lay conceptions of workplace criers are extensive and prototypically organised, through i) observers’ range of ascribed, crier-centric features, and ii) their evaluations of feature prototypicality, which systematically influence implicit cognition. Implications for research examining the interpersonal effects of crying at work are discussed.